The Existence of the Qadiriyah-Naqsabandiyah Order in the Development of the Suryalaya Tasikmalaya Islamic Boarding School - Yamin, Mohamad; Basri, Hasan; Suhartini, Andewi; Meliani, Fitri (Perkumpulan Dosen Tarbiyah Islam Indonesia, 2023)
The existence of the Qadiriyah-Naqsabandiyah orders in Indonesia has played an important and strategic role in the community. The role of the Qadiriyah-Naqsabandiyah orders in the field of education is not limited to aspects of ritual and character building, noble morals, unpretentious personality, and diligent worship, but also to aspects of social solidarity and social sensitivity. This research tries to reveal the role of qadiriyah and naqsabandiyah order education in Pesantren Suryalaya Tasikmalaya. The results of this study revealed that the role of qadiriyah and Naqsabandiyah order education was carried out with an educational approach at the micro and macro levels. At the micro level, the development of education is carried out personally and in small groups through a series of rituals such as baiah, dhikr, khataman, and manaqib. Meanwhile, at the macro level, educational development is carried out in an organized and structured manner through educational institutions and order organizations.